Development of Integrated Maintenance-Quality Policy according to imperfect quality item produced. Issue 12 (2016) - Gouiaa-Mtibaa, Amal; Dellagi, Sofiene; Achour, Zied; Erray, Walid
Abstract: In this paper, we develop integrated models joining non-quality effects and preventive maintenance policy We consider a randomly failing manufacturing system producing one type of product. We note that the output product can be conform or non-conform. In order to reduce random failures of our manufacturing system, a preventive maintenance (PM) policy with minimal repair is applied with non negligible durations of preventive and corrective maintenance actions. Our objective is to determine an optimal integrated maintenance quality strategy taking into account the quality loss rate and the economic impact of reworking activities. In fact, two strategies are developed. The first strategy consists on selling batches at a discount price due to the progressive loss of quality of output products caused by the machine degradation. These non-conforming items will be rejected or sold as second choice products which explains the progressive decrease of the selling price of different batches. The objective of this strategy is to determine the optimal number of batches produced N1 * before each preventive maintenance action maximizing the total profit per time unit (PT1 ). For the second strategy, we propose reworking activities for all deteriorated items observed in a batch in order to improve their quality condition and, consequently, to sell all batches at the best price Pmax . For this second approach, we aim to determine the number of batches produced and reworked N2 * before the preventive maintenance action maximizing the total profit per time unit(PT2 ). Numerical examples are presented in order to illustrate proposed models and a sensitivity study is developed to evaluate the influence of the variation of model's parameters.